Krasnyi kvadrat . Krasnyi kvadrat . Red Square Box . Красный квадрат - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the forthcoming elections to the Parliament of the Russian Federation and the problems of the ruble zone. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation); Volkov, Viacheslav (Deputy Head of the Administration of the Russian President); Chernomyrdin, Viktor Stepanovich (Prime Minister of the Russian Federation) Contributors: Molchanov, Denis (Anchor) Series description: Analytic talk show on the most current political issues. The program is the successor of the program "Vzgliad" ([The View] which in 1991 was renamed into "Red Square." In autumn 1993 "Red Square" was discontinued. Обсуждение предстоящих выборов в парламент Российской Федерации и проблем рублевой зоны. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации); Волков, Вячеслав (Заместитель руководителя Администрации Президента России); Черномырдин, Виктор Степанович (Председатель правительства Российской Федерации) Создатели: Молчанов, Денис (Ведущий/Ведущая) Описание серии: Аналитическое ток-шоу о наиболее важных политических событиях. Программа является наследницей передачи "Взгляд," которая с 1991 года была переименована в "Красный квадрат." Осенью 1993 года "Красный квадрат" был закрыт.